KAJIAN LITERATUR MENGENAI PERMASALAHAN PENDIDIKAN DASAR “KURANGNYA SARANA DAN PRASARANA DI SEKOLAH DASAR" - Allyah Miftahull Jannah; Lutfiah Aini (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
Limited facilities and infrastructure in elementary schools a problem that is still often found in various schools.  The lack of facilities and infrastructure greatly affects school members, especially teachers, in order to achieve their learning goals.  This research was conducted in order to find out what is the cause of the lack of facilities and infrastructure in SD and to find effective solutions to overcome the lack of facilities and infrastructure in SD.  The literature study approach was chose as the research method, by collecting references from various studies that are be accordance of research title, then analyzed in order to draw the essence of the existing references to serve as the main data in the research.  The research results found in the form of obstacles that cause a lack of facilities and infrastructure including: (1) limited human resources;  (2) Limited school funds;  (3) The low awareness of school members in caring for existing facilities and infrastructure;  (4) There is no firmness in responding to violations that have occurred.  Solutions were found from these obstacles is: (1) Imposing strict sanctions on violations;  (2) Request financial assistance from the local government, as well as improve proper and appropriate fund management;  (3) Do creative learning innovations.